Fecal Microbiota Transplantation as a Treatment for Granulomatous Colitis in a French Bulldog: A Case Report - Romano, Felipe S.; Lallo, Maria A.; Romano, Raquel S.; Isidoro, Letícia P. S.; Cardoso, Mariane R.; Sodré, Lylian C.; Melchert, Alessandra [UNESP]; Guimarães-Okamoto, Priscylla T. C. [UNESP]; Pappalardo, Maria C. F.; Amaral, Andressa R.; Vendramini, Thiago H. A. (MDPI, 2025)
Granulomatous colitis, or ulcerative colitis, is an infectious and inflammatory disease that primarily affects the colon and occasionally extends to the ileum, particularly in young Boxer and French Bulldogs. Unlike typical chronic colitis in small animals, the early onset of the disease suggests a genetic predisposition. The condition is characterized by the overgrowth of Escherichia coli, specifically the enteroinvasive variant, which displaces beneficial gut bacteria, contributing to its infectious nature. Secondary dysbiosis and chronic-active inflammation involving histiocytes and other leukocytic infiltrates are prominent features. Clinical manifestations include chronic diarrhea with blood and mucus, frequent tenesmus, and pain, with variable degrees of weight loss depending on disease severity. The final diagnosis is based on clinical history (chronic diarrhea with hematochezia), macroscopic findings from colonoscopy (edema, ulcers, and wall hyperplasia), histopathology (presence of histiocytes), and Escherichia coli growth in culture from a colon fragment. Treatment is guided by colon antibiograms, which often require prolonged antibiotic therapy. Fecal microbiota transplantation (FMT) has emerged as a potential treatment, either as a primary intervention or adjunctive therapy, for conditions such as acute enteritis (e.g., canine parvovirus), dysbiosis, and chronic enteropathies. However, its application to modulate the microbiota and reduce inflammation in granulomatous colitis, potentially leading to longer intervals between relapses, remains an area of ongoing investigation. This is a case report of a French Bulldog diagnosed with ulcerative colitis accompanied by dysbiosis and refractory to standard treatments but sensitive and partially responsive to amikacin. The patient achieved control and sustained improvement in fecal scoring following fecal transplantation. This approach prevented the need for additional antibiotic therapy, ensuring clinical amelioration alongside microbiome restoration.
Keywords: chronic enteropathy; dog; dysbiosis index; histiocytic ulcerative colitis; microbiome